Tocilizumab in COVID-19: Factors Associated With Mortality Before and After Treatment - Sarabia De Ardanaz, Luis; Andreu-Ubero, Jose M.; Navidad-Fuentes, Miriam; Ferrer-González, Miguel Ángel; Ruíz del Valle, Victor; Salcedo-Bellido, Inmaculada; Barrios-Rodríguez, Rocío; Cáliz-Cáliz, Rafael; Requena, Pilar (Frontiers in Pharmacology, 2021)
Tocilizumab (TCZ) has been administered in SARS-CoV-2 pneumonia but the factors associated with mortality before and after treatment remain unclear. Cox regression models were used to estimate the predictors of time to death in a cohort of hospitalized patients with COVID-19 receiving TCZ. In addition, the mean differences between discharged and deceased patients in laboratory parameters measured before and 3, 6 and 9 days after TCZ administration were estimated with weighted generalized estimation equations. The variables associated with time to death were immunosuppression (Hazard Ratio-HR 3.15; 95% confidence interval-CI 1.17, 8.51), diabetes mellitus (HR 2.63; 95% CI 1.23–5.64), age (HR 1.05; 95% CI 1.02–1.09), days since diagnosis until TCZ administration (HR 1.05, 95% CI 1.00–1.09), and platelets (HR 0.27; 95% CI: 0.11, 0.69). In the post-TCZ analysis and compared to discharged patients, deceased patients had more lactate dehydrogenase (p = 0.013), troponin I (p = 0.013), C-reactive protein (p = 0.013), neutrophils (p = 0.024), and fewer platelets (p = 0.013) and lymphocytes (p = 0.013) as well as a lower average PaO2/FiO2 ratio. In conclusion, in COVID-19 diagnosed patients receiving TCZ, early treatment decreased the risk of death, while age, some comorbidities and baseline lower platelet counts increased that risk. After TCZ administration, lower platelet levels were again associated with mortality, together with other laboratory parameters.